Performance analysis and simulation of FMT system in the presence of frequency offset - ZHU Wei-hong; GAO Zhen-ming; GAO You-jun; XU Feng (Tongxin xuebao)
Filtered multitone modulation is one of the filter bank modulation techniques. It exhibits significantly lower spectral overlapping between adjacent subchannels. Therefor it can overcome the sensitivities to carrier frequency offset of the traditional multicarrier modulation, such as OFDM. But per-subchannel equalization should be used to compensate the ISI. The results of theory analysis and computer simulation prove that FMT has a better performance than OFDM in the presence of the carrier frequency offset.